Pengaruh Gross Domestic Product dan Kurs Terhadap Ekspor Negara-Negara ASEAN - Mukarramah, Mukarramah; Zulkarnain, Muhammad (Jurnal Samudra Ekonomika, 2023)
This research was conducted with the aim of knowing the effect of Gross Domestic Product (GDP) and the exchange rate on exports of ASEAN countries. The data used is secondary data sourced from the website of the World Bank. The research population is ASEAN member countries and the samples are from 6 countries, namely Indonesia, Malaysia, Thailand, Singapore, Philippines, and Cambodia. This is because only these countries have complete data for research. Time series data used is from 2004-2021 and cross sections from 6 countries. The data analysis technique used panel data regression. The results showed that Gross Domestic Product (GDP) had a positive and significant effect on exports of ASEAN countries, while the exchange rate had a negative and significant effect on exports of ASEAN countries